Employee commitment effect on organizational effectiveness: Malaysian perspective on a mediator roles in leadership style - Wan Muda, Wan Hanim Nadrah; Isa, Khairunesa; Othman, Nurul Ain; Atim, Asliaty; Goh, Khang Wen (Science Press, 2020)
Leadership style and employee commitment are important human resources in determining organizational performance. It is worth noting that these factors are closely interrelated. To elaborate, implementing a leadership style that caters to the needs of the employees can certainly influence employee commitment levels in an organization. This study aimed to examine the effects of transformational and transactional leadership styles, either as partial or full mediators, on employee commitment to organizational effectiveness. The study involved 130 randomly selected public service officers. Furthermore, three research instruments were used to aid this study, namely, the Multifactor Leadership Questionnaire to measure the respondents’ perceptions of transformational and transactional leadership styles, a three-component model of employee commitment to measure employee commitment, and the Index of Perceived Organizational Effectiveness to measure organizational effectiveness. To determine the effect of a mediator on employee commitment, three regression equations based on the Baron and Kenny model were run through multiple regression analyses. The findings demonstrated that transformational and transactional leadership styles have a partial mediator effect on employee commitment to organizational effectiveness. This study provides some insights into the importance of transformational leadership, especially into the dimension of individualized consideration and the influence of employee commitment on enhancing the effectiveness of an organization.